Basin of upper Paraíba river course – PB, Brazil and its rainfall analysis (Research, Society and Development, 2021)
Precipitation is of extreme importance for the management of water resources, since it is a question of degraded areas and with deforestation for deforestation and the withdrawal of firewood. Frequency analysis was performed on the annual rainfall totals by drawing up the graphs. The scale proposed by Meis et al. (1981), and by the meteorological and CPTEC/INPE nuclei, and provided by Xavier et al. (2005), the annual values ​​that approached the mean value were characterized as intermediaries, and in the scale of annual precipitation values, those that moved away 25% away from the average were considered as very rainy years, and below 25%, like dry years. The application of the Student's t test of significance, pointed out that precipitation data in general are 99% significant. The results showed a tendency of reductions in the rainfall indices, with oscillations of precipitations throughout the series 1962 to 2019, and evidenced the recurrence of maximum values ​​of annual precipitation in the range of 17, 13 and 9 years. It is suggested a study with series of larger years in order to verify the fluctuations and the contributions of the El Niño(a) phenomena in the studied area.